Preparation method of sheet-structured tungsten sulfide carbon catalytic material for hydrogen evolution
By preparing the flake-like structured tungsten sulfide carbon catalytic material, the problem of insufficient catalytic efficiency and stability of existing tungsten sulfide materials is solved, and the effect of high-efficiency hydrogen evolution reaction and multifunctional application is achieved.
Patent Information
- Application Number
- CN202411567810.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
The existing tungsten sulfide materials have shortcomings in catalytic efficiency and stability, and it is difficult to meet the needs of high-efficiency hydrogen evolution reactions.
Using the preparation method of a sheet-like tungsten sulfide carbon catalytic material, a uniform dry powder is formed by mixing ammonium thiotungstate with a carbon source in proportion, dissolved in a solvent, coated on the base material, and then dried and heat treated to form Tungsten sulfide carbon composite material with high catalytic activity and structural stability.
Improves catalytic activity and structural stability, enhances durability and service life under harsh reaction conditions, improves electronic conductivity and light absorption capabilities, and is suitable for multifunctional applications including catalysts, lithium-ion batteries, supercapacitors and the environment Purification and other fields.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of catalytic materials, and in particular relates to a method for preparing a flaky tungsten sulfide carbon catalytic material for hydrogen evolution. Background Art
[0002] With the increasing demand for clean energy, hydrogen has attracted widespread attention as an ideal energy carrier. Tungsten sulfide has become an important catalytic material in hydrogen evolution reaction due to its good photocatalytic and electrocatalytic properties. However, the existing tungsten sulfide materials still have deficiencies in catalytic efficiency and stability, so it is necessary to develop a new and efficient catalytic material. Summary of the invention
[0003] The object of the present invention is to provide a method for preparing a sheet-like tungsten sulfide carbon catalytic material for hydrogen evolution, so as to solve the problems raised in the above background technology.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] A method for preparing a flaky tungsten sulfide carbon catalytic material for hydrogen evolution, the preparation method is as follows:
[0006] Step 1: Raw material preparation:
[0007] Ammonium thiotungstate, carbon source and solvent;
[0008] Step 2: Mixing and soaking:
[0009] A certain amount of ammonium thiotungstate and a carbon source are mixed in proportion to obtain a uniform dry powder;
[0010] Dissolve the mixture in an appropriate amount of solvent and stir thoroughly to obtain a uniform slurry;
[0011] Step 3: Coating and drying:
[0012] Apply the slurry to the surface of the base material to ensure a uniform coating;
[0013] Dry naturally at room temperature or dry at 60°C until the solvent is completely evaporated;
[0014] Step 4: Heat treatment:
[0015] The dried coating material is placed in a nitrogen atmosphere or an inert gas atmosphere and heat treated at a temperature of 600-800° C. for 2-4 hours to promote the formation of tungsten sulfide and the doping of carbon;
[0016] By controlling the heat treatment atmosphere and time, a tungsten sulfide carbon composite material with a sheet structure is obtained;
[0017] Step 5: Post-processing:
[0018] After cooling, use ultrasonic cleaning or other methods to remove unreacted raw materials and impurities;
[0019] The final product is dried to obtain the desired tungsten carbon sulfide catalytic material with a flaky structure.
[0020] Preferably, the specific process of the above step 2 is as follows:
[0021] mix:
[0022] The pre-weighed ammonium thiotungstate and carbon source are mixed in a specific ratio of 1:1 according to the desired catalytic performance;
[0023] Place the two solid raw materials into a dry mixing container and use a blender or stir manually to ensure that they are mixed evenly to form a uniform dry powder;
[0024] soak:
[0025] Transfer the uniform dry powder mixture to a suitable container and add an appropriate amount of solvent to facilitate the dissolution of the material and subsequent reaction;
[0026] Stir the mixture to ensure that all solid particles are wetted by the solvent, and continue stirring until the dry powder is completely dispersed to form a uniform slurry;
[0027] If necessary, the solvent can be heated appropriately to improve solubility and promote mixing reaction, but care must be taken to control the temperature.
[0028] Preferably, the specific process of step three above is as follows:
[0029] Coating:
[0030] Choose a suitable substrate material. Common choices include silicon wafers, glass or metal foil. Make sure the substrate surface is clean and free of contamination to facilitate the adhesion of the coating.
[0031] Spray, brush or spin coat the prepared uniform slurry on the substrate surface. During coating, the coating should be uniform to avoid differences in catalytic performance caused by uneven thickness.
[0032] After coating, please check the uniformity of the coating and make slight adjustments if necessary to ensure the coating thickness is consistent;
[0033] dry:
[0034] Place the substrate material coated with the slurry in a well-ventilated environment and dry it naturally at room temperature until the surface is no longer obviously wet;
[0035] As an alternative, the coated substrate can be placed in an oven and dried at 60°C. The drying time is generally 1-2 hours, and the specific time can be adjusted appropriately according to the humidity conditions, until all solvents are completely evaporated to ensure that the coating is dry.
[0036] During this process, the condition of the coating can be checked regularly to avoid overheating or insufficient drying.
[0037] Preferably, the specific process of step 4 above is as follows:
[0038] Prepare for heat treatment:
[0039] Carefully place the dried coated material into the high temperature furnace, ensuring that the material is evenly distributed so that the heat can be evenly transferred;
[0040] Ensure that the furnace environment is nitrogen atmosphere or other inert gas to prevent the material from reacting with oxygen at high temperatures, which would affect the quality of the final product;
[0041] Set heat treatment conditions:
[0042] Set the furnace temperature between 600℃ and 800℃. The specific temperature can be selected according to the experimental requirements and material properties. Higher temperature helps to promote the formation of tungsten sulfide and carbon doping.
[0043] The heat treatment time is set to 2 to 4 hours, and the length of time can be adjusted according to the required material properties. Generally, a longer heat treatment time can improve the crystallinity and catalytic activity of the material;
[0044] Heat treatment:
[0045] Start the high-temperature furnace and monitor the temperature rise process. When the temperature reaches the set value stably, start timing.
[0046] During the heat treatment process, regularly check the atmosphere and temperature in the furnace to ensure that no abnormal conditions occur;
[0047] cool down:
[0048] After the heat treatment is completed, turn off the furnace and let it cool naturally to room temperature to avoid rapid cooling that may cause thermal stress and cracks in the material;
[0049] After cooling, carefully take out the heat-treated material and observe its appearance and structural changes.
[0050] Preferably, the specific process of step 5 above is as follows:
[0051] cool down:
[0052] After the heat treatment is completed, turn off the furnace and let the treated material cool naturally to room temperature. Avoid using coolants or other methods for rapid cooling to prevent the material from cracking or generating internal stress.
[0053] Cleaning:
[0054] Transfer the cooled material to a suitable cleaning container and clean it using an ultrasonic cleaner. Ultrasonic vibrations can effectively remove unreacted raw materials, impurities, and other undesirable materials.
[0055] Add a cleaning agent (such as deionized water or an appropriate solvent) into the container to ensure that the material is completely covered. The ultrasonic cleaning time can be set to 10 to 30 minutes, depending on the turbidity of the material;
[0056] After cleaning, remove the material, rinse it with deionized water to remove the residue in the cleaning solution, and then gently absorb the surface water;
[0057] dry:
[0058] Place the cleaned material in a dryer or dry it naturally in a well-ventilated environment to ensure that all residual moisture evaporates. You can choose to dry it at 60°C to speed up the drying process.
[0059] After sufficient drying, check the appearance of the material to ensure that it has a flaky structure and a smooth surface;
[0060] Final Product:
[0061] The dried material is the desired flaky tungsten carbon sulfide catalytic material, which can be further characterized and tested for catalytic performance according to experimental requirements.
[0062] Compared with the prior art, the present invention provides a method for preparing a flaky tungsten sulfide carbon catalytic material for hydrogen evolution, which has the following beneficial effects:
[0063] Enhanced catalytic activity:
[0064] Tungsten sulfide has excellent catalytic properties, especially in reactions such as hydrogen evolution, photocatalysis and electrocatalysis. The combination with carbon can further enhance the catalytic activity and promote the reaction.
[0065] Structural stability:
[0066] Flaky tungsten carbon sulfide composites generally have higher mechanical strength and structural stability, and can maintain their shape and performance under harsh reaction conditions, thereby improving the durability and service life of the catalyst.
[0067] Improve electronic conductivity:
[0068] Carbon as a doping material can improve the electronic conductivity of tungsten sulfide, help improve the efficiency of electrocatalytic reactions, and reduce energy losses during charge transfer.
[0069] Excellent light absorption ability:
[0070] Tungsten sulfide has good photocatalytic properties, and the introduction of carbon can expand the light absorption range of the material, enhancing its catalytic activity in the visible light region, which has a positive effect on improving the efficiency of solar energy utilization.
[0071] Versatile Applications:
[0072] This composite material can not only be used as a catalyst, but can also be widely used in lithium-ion batteries, supercapacitors and environmental purification, showing good multifunctionality.
[0073] Economical and environmentally friendly:
[0074] The preparation process of tungsten sulfide carbon composite materials is relatively simple and low in cost. At the same time, the use of natural carbon sources (such as biomass) can reduce environmental impact and contribute to the realization of sustainable development and environmental protection goals.
[0075] Promote hydrogen production reaction:
[0076] This material performs well in catalyzing hydrogen evolution reactions, can effectively reduce the overpotential required during battery operation, and increase the hydrogen production rate, which is of great significance to the development and application of hydrogen energy. DETAILED DESCRIPTION
[0077] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0078] The present invention provides a technical solution:
[0079] A method for preparing a flaky tungsten sulfide carbon catalytic material for hydrogen evolution, the preparation method is as follows:
[0080] Step 1: Raw material preparation:
[0081] Ammonium thiotungstate ((NH4)2WS4), carbon source (such as glucose, freeze-dried carbon black, etc.) and solvent (such as deionized water, alcohol, etc.)
[0082] Step 2: Mixing and soaking:
[0083] A certain amount of ammonium thiotungstate and a carbon source are mixed in proportion to obtain a uniform dry powder;
[0084] Dissolve the mixture in an appropriate amount of solvent and stir thoroughly to obtain a uniform slurry;
[0085] Step 3: Coating and drying:
[0086] Apply the slurry on the surface of a suitable substrate material (such as silicon wafer, glass, etc.) to ensure uniform coating;
[0087] Dry naturally at room temperature or dry at 60°C until the solvent is completely evaporated;
[0088] Step 4: Heat treatment:
[0089] The dried coating material is placed in a nitrogen atmosphere or an inert gas atmosphere and heat treated at an appropriate temperature (such as 600-800° C.) for 2-4 hours to promote the formation of tungsten sulfide and the doping of carbon;
[0090] By controlling the heat treatment atmosphere and time, a tungsten sulfide carbon composite material with a sheet structure is obtained;
[0091] Step 5: Post-processing:
[0092] After cooling, use ultrasonic cleaning or other methods to remove unreacted raw materials and impurities;
[0093] The final product is dried to obtain the desired tungsten carbon sulfide catalytic material with a flaky structure.
[0094] The specific process of step 2 above is as follows:
[0095] mix:
[0096] Pre-weighed ammonium thiotungstate ((NH4)2WS4) and a carbon source (such as glucose or freeze-dried carbon black) are mixed in a specific ratio (e.g., 1:1 or 2:1, adjusted according to the desired catalytic performance);
[0097] Place the two solid raw materials into a dry mixing container and use a blender or stir manually to ensure that they are mixed evenly to form a uniform dry powder;
[0098] soak:
[0099] Transfer the uniform dry powder mixture into a suitable container and add an appropriate amount of solvent (such as deionized water or alcohol) to facilitate the dissolution of the material and subsequent reaction;
[0100] Stir the mixture to ensure that all solid particles are wetted by the solvent, and continue stirring until the dry powder is completely dispersed to form a uniform slurry;
[0101] If necessary, the solvent can be heated appropriately to improve solubility and promote mixing reaction, but care must be taken to control the temperature.
[0102] Through this process, it is possible to ensure that ammonium thiotungstate and the carbon source are fully mixed, thereby improving the efficiency and uniformity of material conversion in subsequent steps. This step is a key preparation link in the entire material preparation process, laying a good foundation for subsequent coating and heat treatment.
[0103] The specific process of step three above is as follows:
[0104] Coating:
[0105] Choose a suitable substrate material, common choices include silicon wafers, glass or metal foil, etc. Make sure the substrate surface is clean and free of contamination to facilitate the adhesion of the coating;
[0106] Spray, brush or spin coat the prepared uniform slurry on the substrate surface. During coating, the coating should be uniform to avoid differences in catalytic performance caused by uneven thickness.
[0107] After coating, check the uniformity of the coating and make slight adjustments if necessary to ensure a consistent coating thickness.
[0108] dry:
[0109] The substrate material coated with the slurry is placed in a well-ventilated environment and dried naturally at room temperature and observed until the surface is no longer obviously wet.
[0110] As an alternative, the coated substrate can be placed in an oven and dried at 60°C. The drying time is generally 1-2 hours. The specific time can be adjusted appropriately according to the humidity conditions until all solvents are completely evaporated to ensure that the coating is dry.
[0111] During this process, the condition of the coating can be checked regularly to avoid overheating or insufficient drying.
[0112] Through this process, the coating material will be stabilized on the substrate, forming a uniform precursor layer, laying the foundation for the subsequent thermal treatment steps, thereby improving the performance of the final catalytic material.
[0113] The specific process of step 4 above is as follows:
[0114] Prepare for heat treatment:
[0115] The dried coated material is carefully placed into the high temperature oven, ensuring that the material is evenly distributed so that the heat can be evenly transferred.
[0116] Make sure the furnace environment is a nitrogen atmosphere or other inert gas (such as argon) to prevent the material from reacting with oxygen at high temperatures, which will affect the quality of the final product.
[0117] Set heat treatment conditions:
[0118] The furnace temperature is set between 600°C and 800°C. The specific temperature can be selected according to the experimental requirements and material properties. Higher temperatures help promote the formation of tungsten sulfide and the doping of carbon.
[0119] The heat treatment time is set to 2 to 4 hours, and the length of time can be adjusted according to the required material properties. Generally, a longer heat treatment time can improve the crystallinity and catalytic activity of the material.
[0120] Heat treatment:
[0121] Start the high-temperature furnace, monitor the temperature rise process, and start timing after ensuring that the temperature stabilizes and reaches the set value.
[0122] During the heat treatment process, the atmosphere and temperature in the furnace are checked regularly to ensure that no abnormal conditions occur.
[0123] cool down:
[0124] After the heat treatment is completed, the furnace is turned off and allowed to cool naturally to room temperature to avoid rapid cooling that may cause thermal stress and cracks in the material.
[0125] After cooling, carefully take out the heat-treated material and observe its appearance and structural changes.
[0126] Through this heat treatment step, the composite material of tungsten sulfide and carbon will form a flaky structure, and its catalytic performance will be significantly improved. Appropriate heat treatment conditions can effectively promote the interaction of materials, so that they can show excellent performance in catalytic reactions such as hydrogen evolution.
[0127] The specific process of step 5 above is as follows:
[0128] cool down:
[0129] After the heat treatment is completed, turn off the furnace and let the treated material cool naturally to room temperature. Avoid using coolants or other methods for rapid cooling to prevent the material from cracking or generating internal stress.
[0130] Cleaning:
[0131] Transfer the cooled material to a suitable cleaning container and clean it using an ultrasonic cleaner. Ultrasonic vibrations can effectively remove unreacted raw materials, impurities and other undesirable materials.
[0132] Add a cleaning agent (such as deionized water or an appropriate solvent) to the container, ensuring that the material is completely covered. The ultrasonic cleaning time can be set for 10 to 30 minutes, depending on the turbidity of the material.
[0133] After cleaning is complete, remove the material, rinse with deionized water to remove any residue from the cleaning solution, and then gently remove the surface water by blotting.
[0134] dry:
[0135] Place the cleaned material in a dryer or dry it naturally in a well-ventilated environment to ensure that all residual moisture evaporates. You can choose to dry it at 60°C to speed up the drying process.
[0136] After sufficient drying, check the appearance of the material to ensure that it has a flaky structure and a smooth surface.
[0137] Final Product:
[0138] The dried material is the desired flaky tungsten carbon sulfide catalytic material. Further property characterization and catalytic performance testing can be carried out according to experimental requirements.
[0139] Through the above post-processing steps, the final obtained sheet-like tungsten sulfide carbon catalyst material is pure and has excellent catalytic performance. This material is suitable for various catalytic reactions, especially in the field of hydrogen precipitation, showing potential application value.
[0140] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a sheet-like tungsten sulfide carbon catalytic material for hydrogen evolution, characterized in that: The preparation method is as follows: Step 1: Raw material preparation: Ammonium thiotungstate, carbon source and solvent; Step 2: Mixing and soaking: A certain amount of ammonium thiotungstate and a carbon source are mixed in proportion to obtain a uniform dry powder; Dissolve the mixture in an appropriate amount of solvent and stir thoroughly to obtain a uniform slurry; Step 3: Coating and drying: Apply the slurry to the surface of the base material to ensure a uniform coating; Dry naturally at room temperature or dry at 60°C until the solvent is completely evaporated; Step 4: Heat treatment: The dried coating material is placed in a nitrogen atmosphere or an inert gas atmosphere and heat treated at a temperature of 600-800° C. for 2-4 hours to promote the formation of tungsten sulfide and the doping of carbon; By controlling the heat treatment atmosphere and time, a tungsten sulfide carbon composite material with a sheet structure is obtained; Step 5: Post-processing: After cooling, use ultrasonic cleaning or other methods to remove unreacted raw materials and impurities; The final product is dried to obtain the desired tungsten carbon sulfide catalytic material with a flaky structure.
2. The method for preparing a sheet-like tungsten sulfide carbon catalytic material for hydrogen evolution according to claim 1, characterized in that: The specific process of step 2 above is as follows: mix: The pre-weighed ammonium thiotungstate and carbon source are mixed in a specific ratio of 1:1 according to the desired catalytic performance; Place the two solid raw materials into a dry mixing container and use a blender or stir manually to ensure that they are mixed evenly to form a uniform dry powder; soak: Transfer the uniform dry powder mixture to a suitable container and add an appropriate amount of solvent to facilitate the dissolution of the material and subsequent reaction; Stir the mixture to ensure that all solid particles are wetted by the solvent, and continue stirring until the dry powder is completely dispersed to form a uniform slurry; If necessary, the solvent can be heated appropriately to improve solubility and promote mixing reaction, but care must be taken to control the temperature.
3. The method for preparing a sheet-like tungsten sulfide carbon catalytic material for hydrogen evolution according to claim 1, characterized in that: The specific process of step three above is as follows: Coating: Choose a suitable substrate material. Common choices include silicon wafers, glass or metal foil. Make sure the substrate surface is clean and free of contamination to facilitate the adhesion of the coating. Spray, brush or spin coat the prepared uniform slurry on the substrate surface. During coating, the coating should be uniform to avoid differences in catalytic performance caused by uneven thickness. After coating, please check the uniformity of the coating and make slight adjustments if necessary to ensure the coating thickness is consistent; dry: Place the substrate material coated with the slurry in a well-ventilated environment and dry it naturally at room temperature until the surface is no longer obviously wet; As an alternative, the coated substrate can be placed in an oven and dried at 60°C. The drying time is generally 1-2 hours, and the specific time can be adjusted appropriately according to the humidity conditions, until all solvents are completely evaporated to ensure that the coating is dry. During this process, the condition of the coating can be checked regularly to avoid overheating or insufficient drying.
4. The method for preparing a sheet-like tungsten sulfide carbon catalytic material for hydrogen evolution according to claim 1, characterized in that: The specific process of step 4 above is as follows: Prepare for heat treatment: Carefully place the dried coated material into the high temperature furnace, ensuring that the material is evenly distributed so that the heat can be evenly transferred; Ensure that the furnace environment is nitrogen atmosphere or other inert gas to prevent the material from reacting with oxygen at high temperatures, which would affect the quality of the final product; Set heat treatment conditions: Set the furnace temperature between 600℃ and 800℃. The specific temperature can be selected according to the experimental requirements and material properties. Higher temperature helps to promote the formation of tungsten sulfide and carbon doping. The heat treatment time is set to 2 to 4 hours, and the length of time can be adjusted according to the required material properties. Generally, a longer heat treatment time can improve the crystallinity and catalytic activity of the material; Heat treatment: Start the high-temperature furnace and monitor the temperature rise process. When the temperature reaches the set value stably, start timing. During the heat treatment process, regularly check the atmosphere and temperature in the furnace to ensure that no abnormal conditions occur; cool down: After the heat treatment is completed, turn off the furnace and let it cool naturally to room temperature to avoid rapid cooling that may cause thermal stress and cracks in the material; After cooling, carefully take out the heat-treated material and observe its appearance and structural changes.
5. The method for preparing a sheet-like tungsten sulfide carbon catalytic material for hydrogen evolution according to claim 1, characterized in that: The specific process of step 5 above is as follows: cool down: After the heat treatment is completed, turn off the furnace and let the treated material cool naturally to room temperature. Avoid using coolants or other methods for rapid cooling to prevent the material from cracking or generating internal stress. Cleaning: Transfer the cooled material to a suitable cleaning container and clean it using an ultrasonic cleaner. Ultrasonic vibrations can effectively remove unreacted raw materials, impurities, and other undesirable materials. Add the cleaning agent into the container, ensuring that the material is completely covered. The ultrasonic cleaning time can be set from 10 to 30 minutes, depending on the turbidity of the material; After cleaning, remove the material, rinse it with deionized water to remove the residue in the cleaning solution, and then gently absorb the surface water; dry: Place the cleaned material in a dryer or dry it naturally in a well-ventilated environment to ensure that all residual moisture evaporates. You can choose to dry it at 60°C to speed up the drying process. After sufficient drying, check the appearance of the material to ensure that it has a flaky structure and a smooth surface; Final Product: The dried material is the desired flaky tungsten carbon sulfide catalytic material, which can be further characterized and tested for catalytic performance according to experimental requirements.